mRNA expression of tumor-associated antigens in melanoma tissues and cell lines - Eichmüller, Stefan B.; Usener, Dirk; Jochim, Anita; Schadendorf, Dirk (Experimental dermatology, 2002)
Abstract: Tumor-associated antigens (TAA) are increasingly used as specific targets for immune therapy of malignant melanoma. The aim of the present study was to provide a basis for selecting the most suitable TAA by analyzing the mRNA expression of a large panel of TAA by RT-PCR and Northern blotting. We have chosen primers differentiating four groups of TAA (MAGE-A, MAGE-B, and two groups of GAGE-genes) and 13 individual TAA (MAGE-A2 and -A3, RAGE-1, -2, -3, and -4, LAGE-1a and -1b, NY-ESO-1, GAGE-1, SSX-2, SCP-1, and cTAGE-1) based on most recent sequence data. In addition, the RAGE-gene family has been separated into its four members by a novel designed nested PCR, which was confirmed by Northern analysis. Furthermore, the chromosomal organization and relationship between the RAGE-family and MOK was analyzed. RAGE-4 mRNA could be shown for the first time to be present in testis tissue. The most frequently expressed TAA were the MAGE-A and the GAGE-3,-4,-5,-6,-8 group, whereas among individual TAA MAGE-A2, -A3, RAGE-1, -3, and LAGE-1a/b were found within most specimens and are thus promising candidates for immune therapy. In comparison, melanoma metastatic specimens and cell lines show similar profiles of TAA expression, but individual TAA differ notably between both types of samples indicating that results from cell lines are not always applicable to tumor specimen.